Ischia and After - Anthony Snodgrass (Cahiers Mondes Anciens)
This short note reminds the important role the meeting “La mort, les morts dans les sociétés anciennes”, which took place in Ischia in 1977, played to establish a long-lasting connection between historical anthropology and classical archaeology.